The intercultural school and the training of the global citizen: the competences of participatory citizenship - Annino, Alessio (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Emancipating from prejudices, dogmatism, fears and mistrust through direct participation is the knot of education for democracy to be solved for a discipline such as education which, in contemporary times, cannot and must never be deaf to change. The essential assumption is that citizenship education needs a solid ethical and moral dimension, as well as a personal and social one, before political and administrative; only when the awareness of the inviolable rights of individuals, men and citizens, of their indifferent protection and awareness of the choices to be made for their exercise emerges from below, then it is possible to organize the step to be taken in the direction of educational and training choices.